Secondary sealing degassing method of sodium ion battery
By using a hard carbon material prepared with pretreatment solution containing sodium chlorite and acetic acid and dopants, the problem of excessive electrolyte loss in the second seal degassing of sodium ion battery is solved, and efficient degassing effect and consistency of battery performance is achieved.
Patent Information
- Application Number
- CN202411718673.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
AI Technical Summary
The existing two-seal and degassing methods of sodium ion batteries lead to excessive loss of electrolyte, affecting the battery's cycle life and consistency of electrical performance.
The biomass coconut shell was pretreated with a pretreatment solution containing sodium chlorite and acetic acid, and mixed with dopants such as sulfur powder, ethylenediamine ditartrate and 1-butyl-2-pyrrolidone for carbonization to prepare a hard carbon material, which was used to prepare the negative electrode sheet of sodium ion battery. This method reduces the loss rate of the electrolyte during the degassing of the second seal.
It improves the first Coulomb efficiency of sodium ion batteries, reduces the loss rate of electrolyte, extends the cycle life of the battery, and improves the consistency of electrical performance.
Smart Images

Figure CN119503773A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a secondary sealing and degassing method for sodium ion batteries. Background Art
[0002] The secondary degassing of sodium-ion batteries has the same definition as that of lithium-ion batteries, both of which refer to the degassing and shaping process after the first charge, with the purpose of making the battery appearance meet the requirements. At the same time, the secondary degassing is to remove the gas generated during the internal formation process of the battery. The gas will also bring out some electrolyte. The electrolyte is a key chemical substance to ensure the normal charging and discharging of the battery. The amount of electrolyte contained in the battery will directly affect the cycle life and electrical performance of the battery. If the amount of electrolyte entrained by the gas during the degassing process exceeds the requirements, the wettability of the electrode cannot be guaranteed and the consistency of battery performance cannot be guaranteed.
[0003] The traditional double-seal degassing method is to place the battery body and the air bag horizontally, and use a bayonet to pierce the air bag for vacuum extraction at room temperature and negative pressure for shaping. The double-seal degassing liquid loss of this method is generally 4-10g, and the amount of electrolyte loss each time is different, the consistency is poor, and often excessive electrolyte loss is caused due to the gas discharge process; in short, the existing double-seal degassing method causes excessive electrolyte loss, low liquid retention rate, inconsistent actual internal liquid retention, serious waste of injected electrolyte, and affect the consistency between batteries. In order to reduce the loss of electrolyte, a lower vacuum degree and a long vacuum delay are usually used. At this time, the degassing effect is not ideal and the production efficiency is low. Therefore, it is very necessary to provide a double-seal degassing method for soft-pack ion batteries with good degassing effect, high battery liquid retention rate, long cycle life, and high electrical performance consistency. Compared with lithium-ion batteries, the negative electrode materials of sodium-ion batteries are mainly hard carbon materials. Compared with graphite, hard carbon is an amorphous carbon material with disordered graphite-like layers, abundant edge and surface defects and unique nanopore structure in its microstructure. The compaction density of hard carbon negative electrode materials (0.9~1.1) is much smaller than that of graphite negative electrode (1.4~1.7), and the compaction of positive electrode materials (ternary layered oxidation) of sodium-ion batteries is also smaller than that of lithium battery ternary materials, that is, the porosity of positive and negative electrode sheets of sodium-ion batteries is much greater than that of lithium-ion batteries, and the amount of electrolyte required will also be greater than that of lithium-ion batteries. The first charge gas production brought by the abundant edge and surface defects of hard carbon negative electrodes and the unique nanopore structure will also be more than that of lithium-ion batteries. It is difficult to effectively balance the loss of electrolyte and the degassing effect by using the traditional two-seal degassing method.
[0004] In order to overcome the problems existing in the above-mentioned technology, the present invention provides a secondary sealing degassing method for a sodium ion battery after formation, so as to achieve an effective degassing effect and reduce the loss of electrolyte. Summary of the invention
[0005] The object of the present invention is to provide a hard carbon material for sodium ion batteries, and a secondary degassing method for sodium ion batteries which can improve the initial coulombic efficiency after being used in sodium ion batteries and reduce the electrolyte loss rate during secondary degassing.
[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A method for preparing a hard carbon material for a sodium ion battery comprises: pretreating biomass coconut shell to obtain a pretreated coconut shell material, then mixing the pretreated coconut shell material with a dopant and performing a carbonization treatment to obtain the hard carbon material; the dopant comprises at least one of sulfur powder, ethylenediamine ditartrate and 1-butyl-2-pyrrolidone. The invention adopts sulfur powder, at least one of ethylenediamine ditartrate and 1-butyl-2-pyrrolidone to prepare a hard carbon material for a sodium ion battery. The hard carbon material for a sodium ion battery has abundant edge and surface defects, and a unique nanopore structure formed under the action of at least one of sulfur powder, ethylenediamine ditartrate and 1-butyl-2-pyrrolidone, and contains a structure of corresponding sulfur elements, nitrogen elements, oxygen elements and carbon elements. The hard carbon material for a sodium ion battery is used with other electrode sheet raw materials to prepare an electrode sheet. After being used to prepare a sodium ion battery, the first coulomb efficiency of the sodium ion battery can be improved, and the loss rate of the electrolyte can be reduced during secondary degassing.
[0007] Preferably, the amount of sulfur powder used is 2-10wt% of the pretreated coconut shell material, the amount of ethylenediamine ditartrate used is 3-15wt% of the pretreated coconut shell material, and the amount of 1-butyl-2-pyrrolidone used is 2-10wt% of the pretreated coconut shell material.
[0008] Preferably, in the carbonization treatment, pre-carbonization is performed at 250-350° C. for 1-3 h, and then heat treatment is performed at 900-1200° C. for 2-6 h in an inert gas atmosphere.
[0009] Preferably, during the pretreatment, the biomass coconut shell is added to the pretreatment liquid and treated at 70-90° C. for 6-24 hours.
[0010] More preferably, the pretreatment liquid is a mixture of sodium chlorite, acetic acid and water, the content of sodium chlorite in the pretreatment liquid is 0.3-1.5wt%, the content of acetic acid in the pretreatment liquid is 0.5-4wt%, and the amount of biomass coconut shell used is 10-30wt% of the pretreatment liquid.
[0011] Preferably, the preparation of the hard carbon material for sodium ion battery includes the preparation of pre-treated coconut shell material and the preparation of the hard carbon material.
[0012] Preferably, in the preparation of the pretreated coconut shell material, the biomass coconut shell is added to the pretreatment liquid, treated at 70-90° C. for 6-24 hours, then filtered and separated, washed and dried to obtain the pretreated coconut shell material. The biomass coconut shell is washed, dried and crushed in one or more steps.
[0013] More preferably, in the preparation of the pretreated coconut shell material, the pretreatment liquid is a mixture of sodium chlorite, acetic acid and water, the content of sodium chlorite in the pretreatment liquid is 0.3-1.5wt%, the content of acetic acid in the pretreatment liquid is 0.5-4wt%, and the amount of biomass coconut shell used is 10-30wt% of the pretreatment liquid.
[0014] Preferably, in the preparation of the hard carbon material, the pretreated coconut shell material is uniformly mixed with the dopant, pre-carbonized at 250-350°C for 1-3h, and then heat treated at 900-1200°C for 2-6h in an inert gas atmosphere to prepare the hard carbon material.
[0015] More preferably, in the preparation of the hard carbon material, the dopant includes at least one of sulfur powder, ethylenediamine tartrate and 1-butyl-2-pyrrolidone, the amount of sulfur powder used is 2-10wt% of the pretreated coconut shell material, the amount of ethylenediamine tartrate used is 3-15wt% of the pretreated coconut shell material, and the amount of 1-butyl-2-pyrrolidone used is 2-10wt% of the pretreated coconut shell material.
[0016] Preferably, p-aminopropionanilide can also be added as a dopant in the preparation of the hard carbon material, and the amount of p-aminopropionanilide used is 2-10wt% of the pretreated coconut shell material. When preparing the hard carbon material, when using at least one of sulfur powder, ethylenediamine ditartrate and 1-butyl-2-pyrrolidone, p-aminopropionanilide can also be used. Under the use of the above reagents, a structure of at least one of sulfur powder, ethylenediamine ditartrate and 1-butyl-2-pyrrolidone and p-aminopropionanilide is formed, further improving the first coulomb efficiency of the sodium ion battery finally prepared, and reducing the electrolyte loss rate.
[0017] The invention discloses a hard carbon material for a sodium ion battery.
[0018] The present invention discloses a sodium ion battery, comprising: the hard carbon material for sodium ion battery.
[0019] Preferably, the positive active materials sodium fluorophosphate, polyvinylidene fluoride and acetylene black are mixed evenly and coated on aluminum foil to make a positive electrode sheet; the hard carbon material for sodium ion battery, carboxymethyl cellulose and acetylene black are mixed evenly and coated on copper foil to make a negative electrode sheet; a sodium ion battery is prepared by using a polypropylene diaphragm as a diaphragm from the positive electrode sheet, the negative electrode sheet and an electrolyte.
[0020] Preferably, in the preparation of the sodium ion battery, the positive active materials sodium fluorophosphate, polyvinylidene fluoride, and acetylene black are mixed evenly and coated on aluminum foil to make a positive electrode sheet; the negative active materials hard carbon material, carboxymethyl cellulose, and acetylene black are mixed evenly and coated on copper foil to make a negative electrode sheet; a polypropylene diaphragm is used as a diaphragm, and a sodium ion battery is prepared from the above-mentioned positive electrode sheet, negative electrode sheet and electrolyte.
[0021] More preferably, in the preparation of the sodium ion battery, sodium fluoride phosphate, polyvinylidene fluoride, and acetylene black are mixed in a mass ratio of 80-90:5-10:5-10, and the positive active material loading on the positive electrode sheet is 15-25 mg cm -2 ; The hard carbon material, carboxymethyl cellulose and acetylene black are mixed in a mass ratio of 80-90:5-10:5-10, and the negative active material loading on the negative electrode sheet is 30-40 mg cm -2 The electrolyte is a NaPF6 solution, which is a mixture of NaPF6, ethylene carbonate and diethyl carbonate. The concentration of NaPF6 in the electrolyte is 0.5-2M. Ethylene carbonate and diethyl carbonate in the electrolyte are mixed in a volume ratio of 1:0.5-2.
[0022] The invention discloses a secondary degassing method for a sodium ion battery, comprising: placing the sodium ion battery in a sealed device, evacuating the sodium ion battery to a vacuum degree 1 of -60-70 kPa; for an air bag part, piercing the air bag with a bayonet and withdrawing the bayonet; continuously evacuating the vacuum, and after the vacuum degree 2 reaches -80-85 kPa, applying a surface pressure of 0.05-0.4 mpa to both sides of the sodium ion battery; continuously evacuating the vacuum, and after the vacuum degree 3 reaches -90-95 kPa, maintaining the state for 2-4 seconds, and heat-sealing an aluminum-plastic film on the side of a sodium ion battery body with upper and lower sealing heads.
[0023] Preferably, after the sodium ion battery is subjected to roller pressing, during the roller pressing process, the sodium ion battery is left to stand at room temperature of 20-40° C. to ensure that the body temperature of the sodium ion battery is consistent with the external room temperature, and then the front and back sides of the sodium ion battery body are roller pressed using a roller.
[0024] Preferably, in the secondary sealing and degassing of the sodium ion battery, the sodium ion battery is placed at a room temperature of 20-40° C. to ensure that the body temperature of the sodium ion battery is consistent with the external room temperature, and then the front and back sides of the sodium ion battery body are rolled by a roller; the sodium ion battery after the rolling treatment is evacuated in a closed device to a vacuum degree 1 of -60~-70 kPa; for the air bag part, the bayonet mouth is located 40~60 mm away from the side of the sodium ion battery body, the air bag is punctured, and the bayonet is retracted; the vacuum is continuously drawn, and after the vacuum degree 2 reaches -80~-85 kPa, a surface pressure of 0.05-0.4 MPa is applied to both sides of the sodium ion battery; the vacuum is continuously drawn, and after the vacuum degree 3 reaches -90~-95 kPa, the state is maintained for 2~4 seconds, and the upper and lower heads heat-seal the aluminum-plastic film at 20-40 mm on the side of the sodium ion battery body, the vacuum state is released, and the secondary sealing and degassing process of the sodium ion battery is completed.
[0025] The present invention uses a pretreatment liquid containing sodium chlorite and acetic acid to pretreat biomass coconut shells, and then mixes with a dopant for carbonization treatment to prepare a hard carbon material. The dopant can be sulfur powder, diethylenediamine tartrate and 1-butyl-2-pyrrolidone. After using sulfur powder, diethylenediamine tartrate and 1-butyl-2-pyrrolidone are further used together to prepare the hard carbon material, and then the hard carbon material is prepared into a negative electrode sheet, and finally the negative electrode sheet is used to make a sodium ion battery, so it has the following beneficial effects: the prepared sodium ion battery has a high first coulomb efficiency and a low electrolyte loss rate. Therefore, the present invention is a hard carbon material for sodium ion batteries, and a second seal degassing method for sodium ion batteries that can improve the first coulomb efficiency after being used in sodium ion batteries and reduce the electrolyte loss rate during second seal degassing. . BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the first Coulomb efficiency diagram.
[0027] Figure 2 This is the electrolyte loss rate diagram. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The following first describes the concepts involved in the present application in conjunction with the accompanying drawings. It should be noted that the following description of each concept is only to make the content of the present application easier to understand, and does not limit the scope of protection of the present application; at the same time, the embodiments and features in the embodiments of the present application can be combined with each other in the absence of conflict. The present application will be described in detail with reference to the accompanying drawings and in conjunction with the embodiments.
[0030] Example 1: A method for preparing a sodium ion battery Preparation of pretreated coconut shell material: add biomass coconut shell to pretreatment liquid, treat at 80℃ for 12h, then filter and separate, wash and dry to obtain pretreated coconut shell material. Biomass coconut shell is washed, dried and crushed. The pretreatment liquid is a mixture of sodium chlorite, acetic acid and water, the content of sodium chlorite in the pretreatment liquid is 1wt%, the content of acetic acid in the pretreatment liquid is 2wt%, and the amount of biomass coconut shell used is 20wt% of the pretreatment liquid.
[0031] Preparation of hard carbon material: The pretreated coconut shell material and the dopant are mixed evenly, pre-carbonized at 300°C for 2h, and then heat treated at 1000°C for 4h under an inert gas atmosphere to prepare the hard carbon material. The dopant includes sulfur powder, ethylenediamine ditartrate and 1-butyl-2-pyrrolidone, the amount of sulfur powder used is 5wt% of the pretreated coconut shell material, the amount of ethylenediamine ditartrate used is 6wt% of the pretreated coconut shell material, and the amount of 1-butyl-2-pyrrolidone used is 3wt% of the pretreated coconut shell material.
[0032] Preparation of sodium ion battery: The positive active materials sodium fluorophosphate alum, polyvinylidene fluoride, and acetylene black are mixed evenly and coated on aluminum foil to make a positive electrode; the negative active materials hard carbon material, carboxymethyl cellulose, and acetylene black are mixed evenly and coated on copper foil to make a negative electrode; a sodium ion battery is prepared from the positive electrode, negative electrode, and electrolyte using a polypropylene diaphragm as a diaphragm. A double seal degassing treatment is used in the preparation of the sodium ion battery. Sodium fluorophosphate alum, polyvinylidene fluoride, and acetylene black are mixed in a mass ratio of 85:7:8, and the positive active material loading on the positive electrode is 20 mg cm -2 ; Hard carbon material, carboxymethyl cellulose, and acetylene black were mixed in a mass ratio of 90:5:5, and the negative active material loading on the negative electrode sheet was 36 mg cm -2 The electrolyte is a NaPF6 solution, which is a mixture of NaPF6, ethylene carbonate and diethyl carbonate. The concentration of NaPF6 in the electrolyte is 1M, and ethylene carbonate and diethyl carbonate are mixed in the electrolyte in a volume ratio of 1:1.
[0033] Secondary sealing and degassing of sodium ion batteries: at room temperature of 25°C, the sodium ion battery is allowed to stand for treatment to ensure that the body temperature of the sodium ion battery is consistent with the external room temperature, and then the front and back sides of the sodium ion battery body are rolled with a roller; the sodium ion battery after rolling is evacuated in a closed device to a vacuum degree 1 of -60kPa; for the air bag part, the bayonet mouth is located 50mm away from the side of the sodium ion battery body, the air bag is punctured, and the bayonet is withdrawn; the vacuum is continuously drawn, and after the vacuum degree 2 reaches -80kpa, a surface pressure of 0.2MPa is applied to both sides of the sodium ion battery; the vacuum is continuously drawn, and after the vacuum degree 3 reaches -90kpa, the state is maintained for 3s, and the upper and lower heads heat-seal the aluminum-plastic film at 30㎜ on the side of the sodium ion battery body, the vacuum state is released, and the secondary sealing and degassing process of the sodium ion battery is completed.
[0034] Example 2: A method for preparing a sodium ion battery The difference between this embodiment and embodiment 1 lies in the preparation of the hard carbon material.
[0035] Preparation of hard carbon material: The pretreated coconut shell material and the dopant are mixed evenly, pre-carbonized at 300°C for 2 hours, and then heat-treated at 1000°C for 4 hours under an inert gas atmosphere to prepare the hard carbon material. The dopant includes sulfur powder, ethylenediamine ditartrate and 1-butyl-2-pyrrolidone, the amount of sulfur powder used is 5wt% of the pretreated coconut shell material, the amount of ethylenediamine ditartrate used is 12wt% of the pretreated coconut shell material, and the amount of 1-butyl-2-pyrrolidone used is 8wt% of the pretreated coconut shell material.
[0036] Example 3: A method for preparing a sodium ion battery The difference between this embodiment and embodiment 1 lies in the preparation of the hard carbon material.
[0037] Preparation of hard carbon material: The pretreated coconut shell material and the dopant are mixed evenly, pre-carbonized at 300°C for 2h, and then heat treated at 1000°C for 4h under an inert gas atmosphere to prepare the hard carbon material. The dopant includes sulfur powder, ethylenediamine ditartrate, 1-butyl-2-pyrrolidone and p-aminopropionamide. The amount of sulfur powder used is 5wt% of the pretreated coconut shell material, the amount of ethylenediamine ditartrate used is 6wt% of the pretreated coconut shell material, the amount of 1-butyl-2-pyrrolidone used is 3wt% of the pretreated coconut shell material, and the amount of p-aminopropionamide used is 4wt% of the pretreated coconut shell material.
[0038] Example 4: A method for preparing a sodium ion battery The difference between this embodiment and embodiment 1 lies in the preparation of the hard carbon material.
[0039] Preparation of hard carbon material: The pretreated coconut shell material and the dopant are mixed evenly, pre-carbonized at 300°C for 2h, and then heat treated at 1000°C for 4h under an inert gas atmosphere to prepare the hard carbon material. The dopant includes sulfur powder, ethylenediamine ditartrate, 1-butyl-2-pyrrolidone and p-aminopropionamide. The amount of sulfur powder used is 5wt% of the pretreated coconut shell material, the amount of ethylenediamine ditartrate used is 6wt% of the pretreated coconut shell material, the amount of 1-butyl-2-pyrrolidone used is 3wt% of the pretreated coconut shell material, and the amount of p-aminopropionamide used is 7wt% of the pretreated coconut shell material.
[0040] Comparative Example 1: A method for preparing a sodium ion battery The difference between this comparative example and Example 1 lies in the preparation of the hard carbon material.
[0041] Preparation of hard carbon material: The pretreated coconut shell material and the dopant are mixed evenly, pre-carbonized at 300°C for 2 hours, and then heat-treated at 1000°C for 4 hours under an inert gas atmosphere to prepare the hard carbon material. The dopant includes sulfur powder, and the amount of sulfur powder used is 5wt% of the pretreated coconut shell material.
[0042] Comparative Example 2: A method for preparing a sodium ion battery The difference between this comparative example and Example 1 lies in the preparation of the hard carbon material.
[0043] Preparation of hard carbon material: The pretreated coconut shell material and the dopant are mixed evenly, pre-carbonized at 300°C for 2 hours, and then heat treated at 1000°C for 4 hours under an inert gas atmosphere to prepare the hard carbon material. The dopant includes sulfur powder and ethylenediamine ditartrate, the amount of sulfur powder used is 5wt% of the pretreated coconut shell material, and the amount of ethylenediamine ditartrate used is 6wt% of the pretreated coconut shell material.
[0044] Comparative Example 3: A method for preparing a sodium ion battery The difference between this comparative example and Example 1 lies in the preparation of the hard carbon material.
[0045] Preparation of hard carbon material: The pretreated coconut shell material and the dopant are mixed evenly, pre-carbonized at 300°C for 2 hours, and then heat-treated at 1000°C for 4 hours under an inert gas atmosphere to prepare the hard carbon material. The dopant includes sulfur powder and 1-butyl-2-pyrrolidone, the amount of sulfur powder used is 5wt% of the pretreated coconut shell material, and the amount of 1-butyl-2-pyrrolidone used is 3wt% of the pretreated coconut shell material.
[0046] Test example: 1. Battery performance test Use a battery charge and discharge tester to perform constant current charge and discharge tests with a voltage of 0.01-2.50V. The battery is first discharged to 0.01V, left for 5 minutes, and then charged to 2.50V. Calculate the first coulomb efficiency, first coulomb efficiency (%) = first discharge specific capacity / first charge specific capacity × 100%.
[0047] The battery performance test results obtained in the above examples 1-4 and comparative example 1 of the present invention are as follows: Figure 1 As shown, S1 is Example 1, S2 is Example 2, S3 is Example 3, S4 is Example 4, D1 is Comparative Example 1, D2 is Comparative Example 2, and D3 is Comparative Example 3. The present invention uses a pretreatment solution containing sodium chlorite and acetic acid to pretreat the biomass coconut shell, and then mixes it with a dopant for carbonization treatment to prepare a hard carbon material. The dopant can be sulfur powder, diethylenediamine tartrate and 1-butyl-2-pyrrolidone. After using sulfur powder, diethylenediamine tartrate and 1-butyl-2-pyrrolidone are further used together to prepare the hard carbon material, and then the hard carbon material is used to prepare a negative The first coulombic efficiency of the battery is high after the negative electrode sheet is made into a battery; when preparing hard carbon materials, increasing the usage of diethylenediamine tartrate and 1-butyl-2-pyrrolidone in the dopant can improve the first coulombic efficiency of the prepared battery; after research, when sulfur powder, diethylenediamine tartrate and 1-butyl-2-pyrrolidone are present in the dopant, p-aminopropionamide can also be added to prepare the hard carbon material, and the first coulombic efficiency of the battery prepared therefrom is further improved, and when the usage of p-aminopropionamide is increased, a sodium ion battery with higher first coulombic efficiency can be obtained.
[0048] 2. Electrolyte loss The sodium ion battery was subjected to secondary sealing and degassing under high vacuum, and the loss of electrolyte was tested according to the methods of the embodiment and comparative example.
[0049] The results of the electrolyte loss rate of the batteries prepared in the above Examples 1-4 and Comparative Example 1 after the second sealing and degassing are as follows: Figure 2As shown, S1 is Example 1, S2 is Example 2, S3 is Example 3, S4 is Example 4, D1 is Comparative Example 1, D2 is Comparative Example 2, and D3 is Comparative Example 3. The present invention uses a pretreatment solution containing sodium chlorite and acetic acid to pretreat the biomass coconut shell, and then mixes it with a dopant for carbonization treatment to prepare a hard carbon material. The dopant can be sulfur powder, diethylenediamine tartrate and 1-butyl-2-pyrrolidone. After using sulfur powder, diethylenediamine tartrate and 1-butyl-2-pyrrolidone are further used together to prepare the hard carbon material, and then the hard carbon material is prepared into a negative electrode sheet, and finally After the battery is made of the negative electrode plate, the loss rate of the electrolyte is small during the second degassing of the battery; when preparing the hard carbon material, when the usage of diethylenediamine tartrate and 1-butyl-2-pyrrolidone in the dopant is increased, the loss rate of the electrolyte can be reduced during the second degassing; after research, when sulfur powder, diethylenediamine tartrate and 1-butyl-2-pyrrolidone are present in the dopant, p-aminopropionamide can also be added to prepare the hard carbon material, and when the battery is prepared from it, the loss rate of the electrolyte can be further reduced during the second degassing, and when the usage of p-aminopropionamide is increased, the loss rate of the electrolyte can be further reduced during the second degassing.
[0050] The embodiments and / or implementation methods described above are only used to illustrate the preferred embodiments and / or implementation methods for realizing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any form. Any technical personnel in this field may make slight changes or modifications to other equivalent embodiments without departing from the scope of the technical means disclosed in the content of the present invention, but they should still be regarded as technologies or embodiments that are essentially the same as the present invention.
[0051] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and its core ideas of this application. The above is only the preferred implementation method of this application. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of this application, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the invention to other occasions without improvement, should be regarded as the scope of protection of this application.
Claims
1. A method for preparing a hard carbon material for a sodium ion battery, comprising: The biomass coconut shell is pretreated to obtain a pretreated coconut shell material, and then the pretreated coconut shell material is mixed with a dopant and then carbonized to obtain a hard carbon material; The doping agent includes at least one of sulfur powder, ethylenediamine tartrate and 1-butyl-2-pyrrolidone.
2. The method for preparing a hard carbon material for a sodium ion battery according to claim 1, characterized in that: The usage amount of the sulfur powder is 2-10wt% of the pretreated coconut shell material, the usage amount of ethylenediamine ditartrate is 3-15wt% of the pretreated coconut shell material, and the usage amount of 1-butyl-2-pyrrolidone is 2-10wt% of the pretreated coconut shell material.
3. The method for preparing a hard carbon material for a sodium ion battery according to claim 1, characterized in that: In the carbonization treatment, pre-carbonization is performed at 250-350° C. for 1-3 h, and then heat treatment is performed at 900-1200° C. for 2-6 h in an inert gas atmosphere.
4. The method for preparing a hard carbon material for a sodium ion battery according to claim 1, characterized in that: In the pretreatment, the biomass coconut shell is added into the pretreatment liquid and treated at 70-90° C. for 6-24 hours.
5. The method for preparing a hard carbon material for sodium ion battery according to claim 4, characterized in that: The pretreatment liquid is a mixture of sodium chlorite, acetic acid and water. The content of sodium chlorite in the pretreatment liquid is 0.3-1.5wt%, the content of acetic acid in the pretreatment liquid is 0.5-4wt%, and the amount of biomass coconut shell used is 10-30wt% of the pretreatment liquid.
6. A hard carbon material for sodium ion battery prepared by the preparation method according to any one of claims 1 to 5.
7. A sodium ion battery comprising: The hard carbon material for sodium ion battery according to claim 6.
8. The method for preparing a sodium ion battery according to claim 7, characterized in that: The positive active materials sodium fluorophosphate, polyvinylidene fluoride and acetylene black are mixed evenly, and coated on aluminum foil to make a positive electrode plate; the hard carbon material for sodium ion battery according to claim 6, carboxymethyl cellulose and acetylene black are mixed evenly, and coated on copper foil to make a negative electrode plate; a sodium ion battery is prepared by using a polypropylene diaphragm as a diaphragm from the above-mentioned positive electrode plate, negative electrode plate and electrolyte.
9. A secondary degassing method for a sodium ion battery, comprising: Place the sodium ion battery in a sealed device and evacuate the device until the vacuum degree 1 is -60~-70kPa; for the air bag part, pierce the air bag with a bayonet and retract the bayonet; continue to evacuate the device until the vacuum degree 2 reaches -80~-85kPa, and then apply a surface pressure of 0.05-0.4mpa to both sides of the sodium ion battery; continue to evacuate the device until the vacuum degree 3 reaches -90~-95kPa, and maintain the state for 2~4s, and then heat-seal the aluminum-plastic film on the side of the sodium ion battery body with the upper and lower sealing heads.
10. A secondary degassing method for a sodium ion battery according to claim 9, characterized in that: After the sodium ion battery is subjected to roller pressing, during the roller pressing process, the sodium ion battery is left to stand at a room temperature of 20-40° C. to ensure that the body temperature of the sodium ion battery is consistent with the external room temperature, and then a roller is used to perform roller pressing on the front and back sides of the sodium ion battery body.